Preparation and evaluation of biocide-loaded particles to control the biofouling zebra mussel, Dreissena polymorpha - Costa, R. (2011)
The freshwater zebra mussel Dreissena polymorpha is a powerful biofouling bivalve, which has tremendous impact on industrial facilities whose operation depends on the intensive use of freshwater, such as waterworks and power stations. The control of the pest in industrial environments remains a major challenge due to low selectivity over non-target organisms and the expense of the large quantities of biocides required. A novel delivery technique involving the encapsulation of a toxin within hundred micron-sized particles, edible for the bivalves, has been recently proposed. This strategy exploits the mussels’ filtration activity and minimises their avoidance responses to certain chemicals, resulting in an increase of their susceptibility to the biocide. In the present paper, which further develops this approach, a new, promising toxin-loaded particulate formulation is presented. The effectiveness of the product as a molluscicide has been demonstrated in laboratory bioassays. Encapsulation was observed to reduce the amount of biocide required to achieve 90% mortality in a 12-h treatment by a factor of approximately three. The dependence of the biocide-loaded particles’ molluscicidal activity on their physical characteristics is also illustrated in this paper by comparing the features of the promising formulation to those of an unsuccessful particulate product.